Sleep Quality and Dyspepsia Syndrome in Students of Public Health Study Program - Qomara, Alfrida Nurul; Yuliawati, Ratna Yuliawati; Kurniasari, Lia (Poltekkes Kemenkes Semarang, 2025)
Research has been done on dyspepsia in adolescents, but it is still rare to analyze the relationship between sleep quality and dyspepsia symptoms. Dyspepsia is a common health issue that affects a significant portion of the population, poor sleep quality may exacerbate gastrointestinal. In this study, we aimed to investigate the relationship between sleep quality and dyspepsia syndrome among students at Universitas Muhammadiyah Kalimantan Timur. This cross-sectional study involved 208 participants from the Public Health program. Data were collected through structured questionnaires Pittsburgh Sleep Quality Index (PSQI) assessing sleep quality and dyspepsia syndrome. Dyspepsia syndrome was measured by Criteria Rome IV (score 4-6 are categorized as dyspepsia syndrome). Ethical approval was obtained, and informed consent was secured from all participant. The primary outcome of the study was the prevalence of dyspepsia syndrome from medical report, which was found in 88.9% of respondents. While, 79.3% of students reported poor sleep quality, with a p-value of 0,000 (p<0.05), indicating a strong association. There are significant associations between sleep quality and dyspepsia syndrome, our study contributes to the understanding of dyspepsia syndrome by highlighting the critical role of sleep quality. This research provides insights into the need for educational interventions aimed at improving sleep hygiene among students.